Hydrogel-cement-based composite material for repairing concrete cracks and preparation method of hydrogel-cement-based composite material

Through the preparation and application of hydrogel-cement-based composite materials, the problems of long repair time, low strength, high toxicity and environmental pollution in the prior art are solved, and the efficient, environmentally friendly and low-cost concrete crack repair effect is achieved.

CN119735400APending Publication Date: 2025-04-01TIANJIN CHENGJIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411849602.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively repair concrete cracks in a short time, and the strength after repair is low, there is a risk of toxicity and environmental pollution, and the operation is complex and costly.

Method used

Hydrogel-cement-based composite materials are used to mix chemical crosslinking agents, ionic crosslinking agents, acrylamide and other materials with ordinary silicate cement, and then stir and polymerize to form hydrogel-cement-based composite materials for injection into concrete cracks for sealing.

Benefits of technology

The composite material has high bonding strength, compression strength and low volume shrinkage. It can block cracks in a short time and restore the original strength of concrete. It is non-toxic and environmentally friendly, simple to operate and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735400A_ABST
    Figure CN119735400A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a hydrogel-cement-based composite material for repairing concrete cracks and a preparation method thereof.The preparation method comprises the steps that 1, a chemical cross-linking agent and / or an ionic cross-linking agent and organic monomer acrylamide are sequentially added into water; 2, Portland cement with the mass being 1.2-2.8 times that of the organic monomer acrylamide is added into the uniform suspension emulsion obtained in the step 1 to be stirred, and a mixed solution is obtained; 3, potassium persulfate with the mass being 0.001-0.003 times that of the organic monomer acrylamide and sodium hydrogen sulfite with the mass being 0.0006-0.0018 times that of the organic monomer acrylamide are added into the mixed solution obtained in the step 2. The invention provides a hydrogel-cement-based composite material for repairing concrete cracks and a preparation method of the hydrogel-cement-based composite material. The hydrogel-cement-based composite material for repairing the concrete cracks can block the concrete cracks in a short time and can effectively restore the concrete to the original strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a hydrogel-cement-based composite material for repairing concrete cracks and a preparation method thereof. Background Art

[0002] Concrete is still the most widely used civil engineering material in the world today because of its high compressive strength, good plasticity, durability and low cost. In the process of concrete service, due to its relatively low tensile strength and more pores, concrete will inevitably have cracks under the influence of dual or even multiple factors such as environment and load (static load, dynamic load), such as temperature cracks, shrinkage cracks and later load cracks. These cracks provide convenient channels for the invasion and damage of harmful media (sulfate erosion, chloride ion erosion, carbonization, etc.), which will not only reduce the strength and durability of concrete, but also may cause the steel bars inside the project to be oxidized, resulting in a large amount of economic losses and safety hazards. Therefore, the maintenance and repair of concrete has not only become a research hotspot and difficulty in the construction industry, but also a key to achieving sustainable development of the concrete industry.

[0003] At present, there are surface treatment, grouting, filling, microbial repair, etc. for treating concrete cracks. Among them, surface treatment and grouting have high requirements for repair materials, and generally use chemical materials such as epoxy resin, methyl methacrylate, and water-soluble polyurethane, which are expensive and toxic. In addition, the repair materials do not contain cement or aggregate, and the strength of the cracks after repair is also low. In addition, the filling method requires the use of pneumatic picks, steel chisels, etc. to expand the cracks to form a groove, and then use the finished repair materials to seal and repair the cracks. The process of crack expansion can easily cause secondary damage to the concrete and affect the structure of the concrete itself. Although the microbial repair method is environmentally friendly and low in cost, its microbial cultivation process is relatively complicated, and the time for microbial repair of cracks is also long. It is difficult to repair the cracks in a short time. There is also a problem of low strength after the cracks are repaired, and it is difficult to restore the original strength of the concrete. Summary of the invention

[0004] The purpose of the present application is to solve the technical problems in the prior art and to provide a hydrogel-cement-based composite material for repairing concrete cracks and a preparation method thereof, which can seal concrete cracks in a relatively short period of time, effectively restore the concrete to its original strength, is non-toxic, does not pollute the environment, and can achieve good economic benefits.

[0005] The technical solution adopted by the embodiment of the present application to solve the technical problems existing in the known technology is:

[0006] A method for preparing a hydrogel-cement-based composite material for repairing concrete cracks, the method comprising the following steps:

[0007] Step 1: adding a chemical crosslinking agent and / or an ionic crosslinking agent, and an organic monomer acrylamide (AM) to deionized water in sequence, and stirring to obtain a uniform suspension emulsion, wherein the mass of the chemical crosslinking agent is 0.01 to 0.03 times the mass of the organic monomer acrylamide (AM), the mass of the ionic crosslinking agent is 0.4 to 0.8 times the mass of the organic monomer acrylamide (AM), and the mass of the organic monomer acrylamide (AM) is 0.25 to 0.45 times the mass of deionized water;

[0008] Step 2: adding ordinary Portland cement (CC) having a mass 1.2 to 2.8 times that of the organic monomer acrylamide (AM) to the uniform suspension emulsion obtained in step 1 and stirring to obtain a mixed solution;

[0009] Step 3: adding potassium persulfate (KPS) having a mass of 0.001 to 0.003 times the mass of organic monomer acrylamide (AM) and sodium bisulfite (SHS) having a mass of 0.0006 to 0.0018 times the mass of organic monomer acrylamide (AM) to the mixed solution obtained in step 2, stirring until completely dissolved, to obtain a hydrogel-cement-based composite material.

[0010] The embodiments of the present application may also adopt the following technical solutions:

[0011] In the above-mentioned method for preparing a hydrogel-cement-based composite material for repairing concrete cracks, further, when the step one adopts a chemical crosslinking agent and an ionic crosslinking agent, the chemical crosslinking agent is N,N-methylenebisacrylamide (BIS), and the ionic crosslinking agent is one or more of calcium chloride (CaCl2), calcium bicarbonate (CaHCO3), magnesium chloride (MgCl2), magnesium bicarbonate (MgHCO3), lithium chloride (LiCl), and barium chloride (BaCl2).

[0012] In the above-mentioned method for preparing a hydrogel-cement-based composite material for repairing concrete cracks, further, when an ionic crosslinking agent is used in step 1, the ionic crosslinking agent is one or more of calcium chloride (CaCl2), calcium bicarbonate (CaHCO3), magnesium chloride (MgCl2), magnesium bicarbonate (MgHCO3), lithium chloride (LiCl), and barium chloride (BaCl2).

[0013] In the above-mentioned method for preparing a hydrogel-cement-based composite material for repairing concrete cracks, further, when a chemical crosslinking agent is used in the step 1, the chemical crosslinking agent is N,N-methylenebisacrylamide (BIS).

[0014] In the above-mentioned method for preparing the hydrogel-cement-based composite material for repairing concrete cracks, further, the temperature in the step 1 is 20-25° C., and the stirring speed is 400-600 r / min.

[0015] In the above-mentioned method for preparing the hydrogel-cement-based composite material for repairing concrete cracks, further, the stirring time in the step 2 is 3 to 5 minutes.

[0016] In the above-mentioned method for preparing a hydrogel-cement-based composite material for repairing concrete cracks, further, in the step three, the ratio of potassium persulfate (KPS) to sodium bisulfite (SHS) is 5:3.

[0017] A hydrogel-cement-based composite material for repairing concrete cracks is prepared by the preparation method of the hydrogel-cement-based composite material for repairing concrete cracks.

[0018] A method for using a hydrogel-cement-based composite material for repairing concrete cracks, the method comprising the following steps:

[0019] The hydrogel-cement-based composite material for repairing concrete cracks is sucked into a syringe, and the syringe is pushed to uniformly inject the hydrogel-cement-based composite material for repairing concrete cracks into the concrete cracks.

[0020] In the above-mentioned method for using the hydrogel-cement-based composite material for repairing concrete cracks, further, the concrete comprises water, cement, gravel, sand and water reducing agent in a mass ratio of 1:(2.17):(6.19):(3.97):(0.018).

[0021] One or more technical solutions provided in the embodiments of the present application have at least the following beneficial effects:

[0022] 1. The composite material of the present invention has high bonding strength, compression strength and low volume shrinkage, can seal concrete cracks in a short time, can effectively restore the concrete to its original strength, and improve the integrity of the concrete structure after the cracks are repaired. In addition, the preparation method of the composite material is simple to operate, and the prepared composite material is non-toxic and does not pollute the environment. Most of the raw materials in the composite material are cement, and the cost is low, so it can be widely used.

[0023] 2. Compared with the currently commonly used surface treatment method and grouting method, the composite material prepared by the present invention is non-toxic and does not pollute the environment. Most of the raw materials used are inorganic cement, and the cost is relatively low. In addition, the compressive strength of the composite material is relatively high, and the strength of the concrete cracks after repair is also relatively high.

[0024] 3. Compared with the currently commonly used filling method, the composite material prepared by the present invention is used to repair concrete cracks, which is simple to operate, does not need to expand the concrete cracks, and will not cause secondary damage to the concrete structure itself.

[0025] 4. Compared with the currently commonly used microbial repair method, the present invention does not require tedious microbial cultivation, and the present invention can seal concrete cracks in a shorter time, the repair cycle is shorter, and the strength of concrete cracks after repair is also higher, which can effectively restore the concrete to its original strength.

[0026] 5. Compared with the currently commonly used epoxy resin grouting materials, the raw material cost of the present invention is lower, the prepared composite material is non-toxic and does not pollute the environment, the operation is relatively simple when repairing cracks, there is no need to set a glue injection nozzle, and there is no need to set glue inlet, exhaust or glue outlet on the cracks. The grouting time is short and the time cost is low.

[0027] 6. The present invention can seal concrete cracks in a relatively short time, can effectively restore concrete to its original strength, is non-toxic, does not pollute the environment, can achieve good economic benefits, has the advantages of simple operation, low time and economic costs, and is environmentally friendly and pollution-free. In addition, the composite material of the present invention will not cause secondary damage to the concrete itself, can seal concrete cracks in a relatively short time, can effectively restore concrete to its original strength, and improve the integrity of the concrete structure after crack repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The technical solutions of the embodiments of the present application will be further described in detail below in conjunction with the accompanying drawings, but it should be noted that these drawings are designed only for explanation purposes and are not intended to limit the scope of the present application. In addition, unless otherwise specified, these drawings are intended only to conceptually illustrate the structural configurations described herein and are not necessarily drawn to scale.

[0029] Figure 1 is the compressive stress-strain curve of the hydrogel-cement-based composite material of Example 1-3;

[0030] Figure 2 This is a polymerization reaction rate diagram of the hydrogel-cement-based composite material of Examples 1-3. DETAILED DESCRIPTION

[0031] The present invention uses calcium chloride (CaCl2), N,N-methylenebisacrylamide (BIS), acrylamide (AM), potassium persulfate (KPS), sodium bisulfite (SHS) and ordinary Portland cement (CC) as basic raw materials, and prepares a hydrogel-cement-based composite material through a simple "one-pot / two-step method". The concrete crack repair composite material applied by the present invention has good bonding strength, can seal concrete cracks in a shorter time, and the interpenetrating cross-linked network structure formed between the hydrogel and the cement also makes the composite material have higher compression strength and lower volume shrinkage, which can effectively restore the concrete to its original strength and improve the integrity of the concrete structure after crack repair.

[0032] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. The following examples are only used to more clearly explain the technical solution of the present invention, so that those skilled in the art can understand and utilize the present invention well, rather than limiting the scope of protection of the present invention. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention.

[0033] Embodiment 1:

[0034] This embodiment includes the following steps:

[0035] Step 1: Place a beaker containing a certain amount of deionized water in a constant temperature water bath magnetic stirrer (water bath temperature is 25°C, stirring speed is 450r / min), then add ionic crosslinking agent calcium chloride (CaCl2) with a mass of 0.7 times the mass of organic monomer acrylamide (AM) and organic monomer acrylamide (AM) with a mass of 0.3 times the mass of deionized water into the beaker in sequence and stir for 3 minutes to obtain a uniform suspension emulsion;

[0036] Step 2: Add ordinary Portland cement (CC) with a mass twice that of the organic monomer acrylamide (AM) into the above emulsion and stir for 3 minutes;

[0037] Step 3: Add the initiator, potassium persulfate (KPS) with a mass of 0.002 times the mass of the organic monomer acrylamide (AM) and sodium bisulfite (SHS) with a mass of 0.0012 times the mass of the organic monomer acrylamide (AM) to the above mixed solution and stir for 30 seconds to obtain a hydrogel-cement-based composite material.

[0038] The method of using this embodiment is:

[0039] A prefabricated crack method was used to make cracks on a concrete test block. The concrete included water, cement, gravel, sand and water reducing agent in a mass ratio of 1:2.17:6.19:3.97:0.018. The size of the concrete test block was 100 mm×100 mm×100 mm. The cracks inside the concrete were through cracks with a length of 80 mm and widths of 1 mm, 1.5 mm and 2 mm, respectively. After the concrete test block was prepared, it was cured in a standard constant temperature and humidity curing box for 28 days before use.

[0040] The prepared hydrogel-cement-based composite material is sucked into a syringe, and then in a concrete test block containing cracks, the syringe is pushed to uniformly inject the hydrogel-cement-based composite material into the cracks.

[0041] With reference to the Technical Conditions for Grouting Materials for Repairing Cracks in Concrete (JC / T333-2011), the volume shrinkage, bonding strength, compressive strength (the compression behavior stops immediately when the compression deformation reaches 65%, and if the material breaks before compression reaches 65%, the compressive strength of the material is characterized by the fracture strength) and polymerization reaction rate of the hydrogel cement-based composite material at 7 days were tested. At the same time, the water permeability coefficient of the concrete cracks was tested 3h, 7d, and 28d after repair, and the compressive strength was tested 7d and 28d after repair. The average compressive strength of the intact concrete test block at 28 days was 36.3MPa, and the average compressive strength of the concrete test blocks with 1mm, 1.5mm, and 2mm wide cracks at 28 days was 9.6MPa, 8.2MPa, and 7.6MPa, respectively.

[0042] The volume shrinkage of the hydrogel cement-based composite material after 7 days was 12.89%, the bonding strength was 2.09 MPa, and the compressive strength was Figure 1 As shown, the compression strength corresponding to the compression deformation of 65% is 38.50MPa, and the polymerization reaction rate is Figure 2 As shown in the figure, the maximum polymerization temperature of 75.9°C was reached at 17 minutes. At this time, the composite material gradually changed from liquid to solid with the polymerization reaction of the hydrogel and basically lost its fluidity.

[0043] The water permeability coefficient of concrete cracks was 0 3h, 7d and 28d after repair.

[0044] The compressive strength of concrete specimens containing cracks with a width of 1mm, 1.5mm, and 2mm after 7 days of repair were 22.5MPa, 21.6MPa, and 16.1MPa, respectively, and the compressive strength recovered to 61.98%, 59.50%, and 44.35% of the original respectively; the compressive strength of concrete specimens containing cracks with a width of 1mm, 1.5mm, and 2mm after 28 days of repair were 35.5MPa, 31.9MPa, and 28.5MPa, respectively, and the compressive strength recovered to 97.80%, 87.88%, and 78.51% of the original respectively.

[0045] Embodiment 2:

[0046] This embodiment includes the following steps:

[0047] Step 1: Place a beaker containing a certain amount of deionized water in a constant temperature water bath magnetic stirrer (water bath temperature is 25°C, stirring speed is 450r / min), then add a chemical crosslinking agent N, N-methylenebisacrylamide (BIS) with a mass of 0.03 times the mass of organic monomer acrylamide (AM) and an organic monomer acrylamide (AM) with a mass of 0.3 times the mass of deionized water into the beaker in sequence and stir for 3 minutes to obtain a uniform suspension emulsion;

[0048] Step 2: Add ordinary Portland cement (CC) with a mass twice that of the organic monomer acrylamide (AM) into the above emulsion and stir for 3 minutes;

[0049] Step 3: Add the initiator, potassium persulfate (KPS) with a mass of 0.002 times the mass of the organic monomer acrylamide (AM) and sodium bisulfite (SHS) with a mass of 0.0012 times the mass of the organic monomer acrylamide (AM) to the above mixed solution and stir for 30 seconds to obtain a hydrogel-cement-based composite material.

[0050] The method of using this embodiment is:

[0051] A prefabricated crack method was used to make cracks on a concrete test block. The concrete included water, cement, gravel, sand and water reducing agent in a mass ratio of 1:2.17:6.19:3.97:0.018. The size of the concrete test block was 100 mm×100 mm×100 mm. The cracks inside the concrete were through cracks with a length of 80 mm and widths of 1 mm, 1.5 mm and 2 mm, respectively. After the concrete test block was prepared, it was cured in a standard constant temperature and humidity curing box for 28 days before use.

[0052] The prepared hydrogel-cement-based composite material is sucked into a syringe, and then in a concrete test block containing cracks, the syringe is pushed to uniformly inject the hydrogel-cement-based composite material into the cracks.

[0053] With reference to the Technical Conditions for Grouting Materials for Repairing Cracks in Concrete (JC / T333-2011), the volume shrinkage, bonding strength, compressive strength (the compression behavior stops immediately when the compression deformation reaches 65%, and if the material breaks before the compression reaches 65%, the compressive strength of the material is characterized by the fracture strength) and polymerization reaction rate of the hydrogel cement-based composite material at 7 days were tested. At the same time, the water permeability coefficient of the concrete cracks was tested 3h, 7d, and 28d after repair, and the compressive strength was tested 7d and 28d after the cracks were repaired. The average compressive strength of the intact concrete test block at 28 days was 36.7MPa, and the average compressive strength of the concrete test blocks with 1mm, 1.5mm, and 2mm wide cracks at 28 days was 9.4MPa, 8.4MPa, and 7.7MPa, respectively.

[0054] The volume shrinkage of the hydrogel cement-based composite material after 7 days was 11.92%, the bonding strength was 1.61 MPa, and the compressive strength was Figure 1 As shown in Figure 2, the fracture occurred when the compression deformation reached 30.16%, and the corresponding compressive strength was 31.95 MPa. The polymerization reaction rate was Figure 2 As shown, the maximum polymerization temperature of 34.4°C was reached at 61 minutes. At this time, the composite material gradually changed from liquid to solid with the polymerization reaction of the hydrogel and basically lost its fluidity.

[0055] The water permeability coefficient of concrete cracks was 0 3h, 7d and 28d after repair.

[0056] The compressive strength of concrete specimens with cracks of 1mm, 1.5mm and 2mm width after 7d of repair were 28.7MPa, 25.4MPa and 22.5MPa respectively, and the compressive strength recovered to 78.20%, 69.21% and 61.31% of the original respectively; the compressive strength of concrete specimens with cracks of 1mm, 1.5mm and 2mm width after 28d of repair were 37.9MPa, 35.5MPa and 34.1MPa respectively, and the compressive strength recovered to 103.27%, 96.73% and 92.92% of the original respectively.

[0057] Embodiment 3:

[0058] This embodiment includes the following steps:

[0059] Step 1: Place a beaker containing a certain amount of deionized water in a constant temperature water bath magnetic stirrer (water bath temperature is 25°C, stirring speed is 450r / min), then add a chemical crosslinking agent N,N-methylenebisacrylamide (BIS) with a mass of 0.03 times the mass of organic monomer acrylamide (AM), an ionic crosslinking agent calcium chloride (CaCl2) with a mass of 0.7 times the mass of organic monomer acrylamide (AM), and an organic monomer acrylamide (AM) with a mass of 0.3 times the mass of deionized water into the beaker in sequence and stir for 3 minutes to obtain a uniform suspension emulsion;

[0060] Step 2: Add ordinary Portland cement (CC) with a mass twice that of the organic monomer acrylamide (AM) into the above emulsion and stir for 3 minutes;

[0061] Step 3: Add the initiator, potassium persulfate (KPS) with a mass of 0.002 times the mass of the organic monomer acrylamide (AM) and sodium bisulfite (SHS) with a mass of 0.0012 times the mass of the organic monomer acrylamide (AM) to the above mixed solution and stir for 30 seconds to obtain a hydrogel-cement-based composite material.

[0062] The method of using this embodiment is:

[0063] A prefabricated crack method was used to make cracks on a concrete test block. The concrete included water, cement, gravel, sand and water reducing agent in a mass ratio of 1:2.17:6.19:3.97:0.018. The size of the concrete test block was 100 mm×100 mm×100 mm. The cracks inside the concrete were through cracks with a length of 80 mm and widths of 1 mm, 1.5 mm and 2 mm, respectively. After the concrete test block was prepared, it was cured in a standard constant temperature and humidity curing box for 28 days before use.

[0064] The prepared hydrogel-cement-based composite material is sucked into a syringe, and then in a concrete test block containing cracks, the syringe is pushed to uniformly inject the hydrogel-cement-based composite material into the cracks.

[0065] With reference to the Technical Conditions for Grouting Materials for Repairing Cracks in Concrete (JC / T333-2011), the volume shrinkage, bonding strength, compressive strength (the compression behavior stops immediately when the compression deformation reaches 65%, and if the material breaks before the compression reaches 65%, the fracture strength is used to characterize the compressive strength of the material) and polymerization reaction rate of the hydrogel cement-based composite material were tested at 7 days. At the same time, the water permeability coefficient of the concrete cracks was tested 3h, 7d, and 28d after repair, and the compressive strength was tested 7d and 28d after the cracks were repaired. The average compressive strength of the intact concrete test block at 28 days was 36.5MPa, and the average compressive strength of the concrete test blocks with 1mm, 1.5mm, and 2mm wide cracks at 28 days was 9.4MPa, 8.3MPa, and 7.8MPa, respectively.

[0066] The volume shrinkage of the hydrogel cement-based composite material after 7 days was 11.40%, the bonding strength was 2.03 MPa, and the compressive strength was Figure 1 As shown in the figure, the compression strength corresponding to the compression deformation of 65% is 61.61MPa. Figure 2 As shown, the maximum polymerization temperature of 92.9°C was reached at 6 minutes. At this time, the composite material gradually changed from liquid to solid with the polymerization reaction of the hydrogel and basically lost its fluidity.

[0067] The water permeability coefficient of concrete cracks was 0 3h, 7d and 28d after repair.

[0068] The compressive strength of concrete specimens with cracks of 1mm, 1.5mm and 2mm width after repair for 7 days were 30.9MPa, 30.3MPa and 29.9MPa, respectively, and the compressive strength recovered to 84.66%, 83.01% and 81.92% of the original respectively; the compressive strength of concrete specimens with cracks of 1mm, 1.5mm and 2mm width after repair for 28 days were 40.9MPa, 38.7MPa and 37.9MPa, respectively, and the compressive strength recovered to 112.05%, 106.03% and 103.84% of the original respectively.

[0069] The hydrogel-cement-based composite material of the present embodiment is a composite material formed by dual crosslinking of chemical crosslinking and ionic crosslinking. The structure itself is stronger and the volume shrinkage rate is lower. Therefore, the dual crosslinked composite material is more effective in repairing cracks.

[0070] But whether it is a chemical, ionic double cross-linked composite material, an ionic cross-linked composite material or a chemical cross-linked composite material, its volume shrinkage is about 12%, the bonding strength is greater than 1.5MPa, and the water permeability coefficient of the concrete repaired after 3h, 7d and 28d using the composite material is 0, which shows that the composite material of the present invention can not only seal the concrete cracks in a relatively short time, but also has a certain durability. When the hydrogel cement-based composite material cross-linked in these three ways is used to repair concrete with 1mm, 1.5mm and 2mm wide cracks, its 7d compressive strength recovery rate basically exceeds the original 50%, and the 28d strength can basically recover to the original strength, or even exceed the original strength. Generally speaking, the double cross-linked hydrogel cement-based composite material with higher compressive strength and lower volume shrinkage has the best effect on the repair of concrete cracks. It can not only seal the concrete cracks in a relatively short time, but also its 28d strength recovery rate exceeds 100%.

[0071] In summary, the hydrogel-cement-based composite material for repairing concrete cracks and the preparation method thereof provided by the present invention can seal concrete cracks in a relatively short period of time, effectively restore the concrete to its original strength, and improve the integrity of the concrete structure after the cracks are repaired. In addition, the present invention is simple to operate, has low time and economic costs, and will not cause secondary damage to the concrete itself when repairing concrete cracks.

[0072] The above embodiments describe the present invention in detail, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a hydrogel-cement-based composite material for repairing concrete cracks, characterized in that: The preparation method of the hydrogel-cement-based composite material for repairing concrete cracks comprises the following steps: Step 1: adding a chemical crosslinking agent and / or an ionic crosslinking agent and an organic monomer acrylamide to water in sequence, and stirring to obtain a uniform suspension emulsion, wherein the mass of the chemical crosslinking agent is 0.01 to 0.03 times the mass of the organic monomer acrylamide, the mass of the ionic crosslinking agent is 0.4 to 0.8 times the mass of the organic monomer acrylamide, and the mass of the organic monomer acrylamide is 0.25 to 0.45 times the mass of water; Step 2: adding silicate cement having a mass 1.2 to 2.8 times that of the organic monomer acrylamide to the uniform suspension emulsion obtained in step 1 and stirring to obtain a mixed solution; Step 3: adding potassium persulfate having a mass of 0.001 to 0.003 times the mass of the organic monomer acrylamide and sodium bisulfite having a mass of 0.0006 to 0.0018 times the mass of the organic monomer acrylamide to the mixed solution obtained in step 2, stirring until completely dissolved, to obtain a hydrogel-cement-based composite material.

2. The method for preparing the hydrogel-cement-based composite material for repairing concrete cracks according to claim 1, characterized in that: When a chemical crosslinking agent and an ionic crosslinking agent are used in step 1, the chemical crosslinking agent is N,N-methylenebisacrylamide, and the ionic crosslinking agent is one or more of calcium chloride, calcium bicarbonate, magnesium chloride, magnesium bicarbonate, lithium chloride, and barium chloride.

3. The method for preparing the hydrogel-cement-based composite material for repairing concrete cracks according to claim 1, characterized in that: When an ionic crosslinking agent is used in step 1, the ionic crosslinking agent is one or more of calcium chloride, calcium bicarbonate, magnesium chloride, magnesium bicarbonate, lithium chloride, and barium chloride.

4. The method for preparing the hydrogel-cement-based composite material for repairing concrete cracks according to claim 1, characterized in that: When a chemical cross-linking agent is used in step 1, the chemical cross-linking agent is N,N-methylenebisacrylamide.

5. The method for preparing the hydrogel-cement-based composite material for repairing concrete cracks according to claim 1, characterized in that: The water in step 1 is deionized water, the temperature is 20-25° C., and the stirring speed is 400-600 r / min.

6. The method for preparing a hydrogel-cement-based composite material for repairing concrete cracks according to claim 1, characterized in that: The stirring time in step 2 is 3 to 5 minutes.

7. The method for preparing a hydrogel-cement-based composite material for repairing concrete cracks according to claim 1, characterized in that: The ratio of potassium persulfate to sodium bisulfite in step 3 is 5:

3.

8. A hydrogel-cement-based composite material for repairing concrete cracks, characterized in that: The hydrogel-cement-based composite material for repairing concrete cracks is prepared by the preparation method of the hydrogel-cement-based composite material for repairing concrete cracks according to any one of claims 1 to 7.

9. A method for using a hydrogel-cement-based composite material for repairing concrete cracks, characterized in that The method for using the hydrogel-cement-based composite material for repairing concrete cracks comprises the following steps: The hydrogel-cement-based composite material for repairing concrete cracks according to claim 8 is sucked into a syringe, and the syringe is pushed to uniformly inject the hydrogel-cement-based composite material for repairing concrete cracks into the concrete crack.

10. The method for using the hydrogel-cement-based composite material for repairing concrete cracks according to claim 9, characterized in that: The concrete includes water, cement, gravel, sand and water reducing agent in a mass ratio of 1:(2.17):(6.19):(3.97):(0.018).